Baby Blues Syndrome in the Qur'an: A Resilience Study of Maryam's Story - Safitri, Novita; Rusli, Ris'an; Apriyanti, Apriyanti; Hasanah, Uswatun; Kusnadi, Kusnadi (Jurnal Ushuluddin, 2025)
This study examines the story of Maryam in the Qur'an as a model of resilience in addressing postpartum depression. The purpose of this research is to identify aspects of mental resilience, utilizing Grotberg's resilience theory, that can be applied to postpartum mothers. The study employs a thematic interpretation method combined with a literature review approach. Primary data sources were gathered from Qur'anic verses, while secondary sources included tafsir (Qur'anic exegesis) books, scientific journals, and articles related to mental health. The results of the study indicate that Maryam overcame physical, emotional, and social challenges with extraordinary resilience through spiritual support (I Have), strength of faith and optimism (I Am), and adaptability and problem-solving skills (I Can). The implementation of these values includes spiritual practices such as prayer, remembrance of Allah, and reading the Qur'an, as well as the importance of social support from family and the community. This study contributes new insights to the interdisciplinary fields of Islamic spirituality and psychology and offers practical guidance for postpartum mothers in managing their emotions. This approach provides a more holistic perspective on supporting maternal mental well-being by integrating spiritual and psychological aspects for postpartum recovery.